SOSIALISASI KOMPRES DINGIN DAUN KUBIS DALAM MENURUNKAN INTENSITAS NYERI PAYUDARA - Ika Nur Saputri; Raini Panjaitan; Novita Br Ginting Munthe; Basyariah Lubis; Irma Nurianti; Yuni Adelia; Sri Melda Br. Bangun (JURNAL PENGMAS KESTRA (JPK), 2021)
Breastfeeding problems that often arise in the postpartum period are breast engorgement or also called breast milk dams. Cabbage leaf cold compress can have an effect in reducing the intensity and swelling of the breast, cabbage leaf contains sinigrin (allylisothiocyanate) rapine, mustardoil, magnesium, oxylate, sulfur and has antibiotic, anti-irritating, and anti-inflammatory properties. The content in cabbage leaves can help increase blood flow to the area of ​​swelling, and expand capillary networks so that it has properties that can be used to reduce swelling and inflammation of the breast so that it affects the smoothness of milk. This community service is carried out on postpartum mothers. The first preparation before going into the field was discussing the material that would be socialized to postpartum mothers. The next preparation is making banners that facilitate the socialization process. Cabbage leaf cold compresses are proven to reduce breast pain. Cabbage leaves contain sulfur and antibiotic properties that can reduce the pain of breast engorgement and reduce inflammation in the breast. In addition, processed cabbage leaves can be sold to generate income for postpartum mothers.